Efforts to Improve Financial Management Capabilities through Digital-Based Literacy and Inclusion for Coffee Shop Entrepreneurs in Medan City - Siregar, Fhikry Ahmad Halomoan; Harahap, Baginda; Nurhadi, A'an; Pohan, Adekasna Rosadi; Prasetyo, Imam (Yayasan Riset dan Pengembangan Intelektual, 2024)
The purpose of the study was to determine the effect of financial inclusion and digital-based financial literacy on the financial management capabilities of Coffee Shop Entrepreneurs in Medan City. This research method is quantitative research. The design of this study uses a cross-sectional design method with a sampling technique using purposive sampling. This study uses data analysis with the Partial Least Square approach (Data were collected using questionnaires, literature studies, observations, interviews, Focus Group Discussions. The results of the study show that financial inclusion and digital-based financial literacy have an effect on the financial management capabilities of Coffee Shop Entrepreneurs in Medan City.